Filipino "militics" (Filipino Military Politics). - Nafarrete, Perpetuo G. III
The study focuses on a relatively new phenomenon in Filipino politics -- "militics" (military politics). (p)The library research was conducted in order to trace the historical development of militics in the Philippines, to analyze the nature of Filipino militics, to determine the factors that led to the politicization of the Filipino military, and to analyze the bearing of the politicization of the military on the Filipino politics. (p)The study makes of pertinent literature on militics written by such noted luminaries as Abrahamsson, Feit, Huntington, Janowitz, McCoy, Smith, Welch, etc. Views called from the works of noted Filipino social scientists such as Abinales, Hernandez, Miranda, Nemenzo, etc. were taken into perusal consideration. (p)The study concludes that the historical development and nature of Filipino militics may be traced to Marcos' ascendance to power as well as through the birth and development of the Armed Forces of the Philippines through the years. It also concludes that the bearing of the politicization of the military on Filipino militics is tremendous. It altered the tradition of civilian supremacy over the military. It paved the way for a new dimension in filipino politics -- apart from the politics of people power -- the politics of coup d' etat. (p)Men who adopt the profession of arms submit of their own free will to a law of pertual constraint of their own accord. They resist their right to live where they choose, to say what they think, to dress as they like, it needs but an order to settle them from their family and dislocate their normal lives. (p)In the world of command, they must rise, march, run, endure bad weather, go without sleep or food, be isolated in some distant post, work until they drop. They have ceased to be the master of their fate. If they drop in their tracks, if their ashes are scattered to the four winds, that is all part and parcel of their job. (Gen. Charles de Gaulle) (p)No profession cost than that of soldiery. For the soldier, gaining an ounce of peace may mean for him --sweat, blood, tears, and even his own life. (Anonymous)